Immigration policy review and comparison of Germany, Italy and the Netherlands - Vo, Ha An (2016)
The thesis reviews and provides comparison of immigration policies of Germany, Italy and the Netherlands from post-WW2 years to the late 1990s. With regards to the different historical, cultural and social background of each country the dissertation thesis defines the unique approach to immigration and perception of immigrants in each country. The ultimate aim of the thesis is to explain the circumstances that lead to the specific events in the history of immigration policies of the countries in question and bring comprehension in this often overlooked matter.